Proceedings of the 34th Design Automation Conference
DOI: 10.1109/dac.1997.597167
|View full text |Cite
|
Sign up to set email alerts
|

CELLERITY: A Fully Automatic Layout Synthesis System For Standard Cell Libraries

Abstract: This paper describes a fully automatic standard-cell layout synthesis system, CELLERITY: The system is JexibEe in supporting a wide variety ofprocess technologies and a range of library template styles. The tool is fully automatic and provides several options to the user to customize the layout template. The tool considers performance and yield and generates dense, design-rule correct layouts. Experimental results indicate that the area of CELLERlTY-generated standard cells is competitive with manually designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
(4 reference statements)
0
23
0
Order By: Relevance
“…The synthesis of cell libraries has been one of the targets for design automation since long ago [2,3]. With large feature dimensions, the layout elements could be placed with very simple design rules.…”
Section: A Cell Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of cell libraries has been one of the targets for design automation since long ago [2,3]. With large feature dimensions, the layout elements could be placed with very simple design rules.…”
Section: A Cell Synthesismentioning
confidence: 99%
“…For standard cells, in which area is limited by the cell height, compaction was often integrated to optimize area [3].…”
Section: Cell Routingmentioning
confidence: 99%
“…We will refer to this as pin-to-wire routing. One such motivation is to enable routing by abutment, in the manner that standard cell-based ASICs connect power rails in rows of cells [2], or that a datapath layout generator might abut stages in a layout [3]. In the FPGA context, this idea translates to having preplaced and pre-routed modules that could connect together by abutment, presuming efficient routing to and from specific wire segments in an FPGA routing channel is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The recent significant progress in automated cell-layout generation [1][2] has made transistorlevel optimization a feasible and practical solution. The latest researches have demonstrated that such optimization techniques could be successfully applied to real design projects and achieved significant performance improvements [3] [4].…”
Section: Introductionmentioning
confidence: 99%